The Implementation Of Problem Based Learning (PBL) Model Assisted By Wordwall To Improve Students Achievement At SMP Negeri 12 Padang - Ramadhana Putri, Widya; Yanto, Febri; Nuzullah Putri, Azza; Evita Putri, Rahmah (Pendidikan IPA, FMIPA, UNP, 2025)
This study examined the effect of implementing the Problem-Based Learning (PBL) model assisted by Wordwall on the learning achievement of seventh-grade students at SMPN 12 Padang. The research employed a quasi-experimental design with a non-equivalent control group. The population consisted of all seventh-grade students, while the sample was selected purposively, comprising classes VII-5 and VII-7. The experimental group received instruction through the PBL model integrated with Wordwall activities, whereas the control group was taught using conventional methods. Data were collected using multiple-choice tests administered as pretests and posttests, and analyzed using Microsoft Excel. The results revealed a significant difference in the average scores between the experimental and control groups. The t-test analysis yielded a calculated t-value of 2.3027, which exceeded the critical t-value of 1.9964, indicating the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (Hₐ). These findings suggest that the use of the PBL model assisted by Wordwall significantly enhances students’ learning achievement in seventh-grade science at SMPN 12 Padang.